Effect of subclinical zinc deficiency in lambs on nitrogen retention, productive and hematological parameters (Veterinary Science, 2021)
The objective of this trial was to study the effect of subclinical zinc (Zn) deficiency in lambs on productive variables, nitrogen (N) balance and hematological parameters. Ten Corriedale lambs, with an average weight of 10.09 kg, were randomly assigned to two groups: Basal (B, 10 ppm Zn) and Supplemented with 30 ppm Zn (Z). The trial lasted 20 weeks. The animals were weighed every 4 weeks. Also with this periodicity, they were bled by jugular venipuncture. In weeks 6 and 20 the apparent dry matter digestibility (ADMD) and N balance were evaluated. At the end of the test the wool production and quality were measured.The weight gain and wool quality were similar in both groups, while wool production was 37.4% higher in group Z. According to the first balance period, ADMD was similar in both groups, but the retention of N was significantly higher in group Z than in group B (5.53 vs 4.03 g/day). In the second balance period there was a similar trend. There were no differencies between groups on hematocrit, hemoglobin concentration, red blood cells, total leukocytes, lymphocytes and neutrophils number. These results suggest that subclinical Zn deficiency reduces wool production, which may be related to lower proteinsynthesis.
Keywords: zinc deficiency, lambs, wool production, nitrogen retention, hematology.